2005
DOI: 10.1191/0267659105pf838oa
|View full text |Cite
|
Sign up to set email alerts
|

Seventy-two hour gas exchange performance and hemodynamic properties of NOVALUNG®iLA as a gas exchanger for arteriovenous carbon dioxide removal

Abstract: NOVALUNG iLA can provide near total CO2 removal with Qb 1-2 L/min, Qg 5 L/min, and minimal flow resistance (3.88+/-0.82 mmHg/L/min). PaCO2 correlates with CO2 removal and is dependent on Qb and Qg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…The present in vivo measurements confirmed these considerations as well as animal data previously published [10,11]. A 2-Fr increase in cannula size resulted in an additional flow of ,300 mL?min -1 .…”
Section: Discussionsupporting
confidence: 91%
“…The present in vivo measurements confirmed these considerations as well as animal data previously published [10,11]. A 2-Fr increase in cannula size resulted in an additional flow of ,300 mL?min -1 .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, increasing blood flow at constant sweep gas flow led to a less pronounced, but significant increase in CO 2 transfer together with a decrease in PaCO 2 . These findings are in line with the iLA sheep models of Jayroe et al and Zhou et al [1,13], who both demonstrated increasing CO 2 removal by raising blood flow up to 1.4 and 1.6 L/min, respectively. Our data suggest an increase in CO 2 elimination up to even 2.0 mL/min of blood flow.…”
Section: Discussionsupporting
confidence: 87%
“…By using the same gas exchange membrane as in our study (iLA, Novalung, Germany) in a pumpless arterio-venous configuration, comparable results have been generated in a sheep model [13] as well as in patients with acute lung failure [3]. Zhou and co-workers demonstrated increasing CO 2 removal with increasing sweep gas flow up to 10 L/min, while a further increase was associated with only minimally higher rate of CO 2 removal [13].…”
Section: Discussionsupporting
confidence: 72%
“…A variety of recent studies have investigated the efficacy and safety of pumpless arterovenous devices to remove CO 2 [14-17], which offer several advantages over ECMO: reduced bleeding risk, less time consumption, lower cost, no mechanical damage of blood components, and no need for a perfusionist staff. But these techniques also have their disadvantages, the most common being ischaemia of the lower limb after prolonged femoral arterial cannulation, increase of left-to-right shunt (thus excluding patients with cardiac failure), and no direct blood flow control.…”
Section: Discussionmentioning
confidence: 99%